Comparison of the Effectiveness of Schema Therapy and Cognitive-Behavioral Therapy Before Marriage on Emotional Maturity and Body Image of Single Women - HiradAsa, Mahrokh; Goodarzi, Kourosh; Roozbahani, Mehdi; Saedi, Sara; Tanha, Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The increasing delay in the age of marriage and the decreasing interest and willingness of single women to marry have led to a rise in the age of marriage, resulting in an increase in the number of single women with higher ages. This study aimed to compare the effectiveness of schema therapy and cognitive-behavioral therapy before marriage on the emotional maturity and body image of single women.Methods and Materials: This quasi-experimental study employed a pre-test and post-test design with a non-equivalent control group. The study population included single women from District 1 of Tehran in 2022. The research sample consisted of 60 participants selected through convenience sampling based on a call from the study population, and they were randomly assigned to two experimental groups and one control group. Participants completed the Emotional Maturity Questionnaire (Yashvir Singh and Mahesh Bhargava, 1991) and the Body Image Questionnaire (Fisher, 1970) before the intervention, after the intervention, and at follow-up. The first experimental group received schema therapy and the second experimental group received cognitive-behavioral therapy in eight 90-minute sessions based on the schema therapy protocol (Leahy, 2013) and the cognitive-behavioral therapy protocol (Beck, 1964), respectively. Data were analyzed using one-way ANCOVA and one-way ANOVA with post hoc tests using SPSS software.Findings: The results indicated that schema therapy and cognitive-behavioral therapy significantly (mean difference with p < 0.05) reduced emotional maturity instability and improved body image (mean difference with p < 0.05) in single women.Conclusion: Based on the findings, it is concluded that schema therapy before marriage and cognitive-behavioral therapy can be effective therapeutic methods for improving the emotional maturity and body image of single women and can be used as important and key interventions in the pre-marriage domain.